2015
DOI: 10.1103/physrevlett.115.207003
|View full text |Cite
|
Sign up to set email alerts
|

Strong Coupling Superconductivity in the Vicinity of the Structural Quantum Critical Point in(CaxSr1x)

Abstract: The family of the superconducting quasiskutterudites (Ca(x)Sr(1-x))(3)Rh(4)Sn(13) features a structural quantum critical point at x(c)=0.9, around which a dome-shaped variation of the superconducting transition temperature T(c) is found. Using specific heat, we probe the normal and the superconducting states of the entire series straddling the quantum critical point. Our analysis indicates a significant lowering of the effective Debye temperature on approaching x(c), which we interpret as a result of phonon so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
149
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(158 citation statements)
references
References 54 publications
9
149
0
Order By: Relevance
“…Superconducting stannides [1,2] with stoichiometry A 3 T 4 Sn 13 (A = La, Sr, Ca and T = Co, Rh, Ir) have received a renewed attention owing to the discovery of a structural transition that can be tuned to 0 K [3][4][5]. In Sr 3 Ir 4 Sn 13 and Sr 3 Rh 4 Sn 13 , the structural transition occurs at T * 147 [3,6] and 138 K [4,7], respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Superconducting stannides [1,2] with stoichiometry A 3 T 4 Sn 13 (A = La, Sr, Ca and T = Co, Rh, Ir) have received a renewed attention owing to the discovery of a structural transition that can be tuned to 0 K [3][4][5]. In Sr 3 Ir 4 Sn 13 and Sr 3 Rh 4 Sn 13 , the structural transition occurs at T * 147 [3,6] and 138 K [4,7], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In Sr 3 Ir 4 Sn 13 and Sr 3 Rh 4 Sn 13 , the structural transition occurs at T * 147 [3,6] and 138 K [4,7], respectively. In these systems, a pronounced anomaly can be seen at T * in various physical properties [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], including the electrical resistivity, the magnetic susceptibility and the specific heat. With applied pressure or the substitution of Sr by Ca, i.e., (Ca x Sr 1−x ) 3 Ir 4 Sn 13 and (Ca x Sr 1−x ) 3 Rh 4 Sn 13 , T * decreases rapidly, accompanied by a moderate increase in the superconducting transition temperature T c , which peaks near the composition/pressure where T * extrapolates to 0 K. The phase diagrams constructed thus highly resemble the ones constructed for many topical superconductors found in the vicinity of a magnetic quantum critical point [29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, in this case, it can easily be explained within the standard BCS-based theories: the gap associated with the CDW closes at the critical point, resulting in an increase of N ( F ), which, in turn, leads to an increase of the SC transition temperature T c . As a consequence, the dependence of T c on the tuning parameter is usually rather weak in the non-CDW regime beyond the critical point 16,17,[20][21][22][23] . There is currently no clear evidence that quantum critical fluctuations associated with the CDW QCP have any effect on the SC 24 .…”
Section: Substituting Pd For Pt Suppressesmentioning
confidence: 99%
“…Recent work on members of the stannide superconducting family A 3 T 4 Sn 13 (A = La,Sr,Ca; T = Ir,Rh) [5][6][7][8][9][10][11][12][13] is proving to be interesting in this context. Studies of Sr 3 Ir 4 Sn 13 have shown that the material undergoes a continuous second-order phase transition at a temperature T * ∼ 147 K, which is observed in a range of transport, spectroscopic, and thermodynamic measurements [14,15].…”
mentioning
confidence: 99%